PERJALANAN PT PABRIK ES SIANTAR DALAM MENGHADAPI ERA DIGITAL: SEJARAH, FILOSOFI, DAN EKSISTENSI MINUMAN CAP BADAK - Elias Jaya Zega; Monica Claudia Siahaan; Lila Pelita Hati; Lestari Dara Cinta Utami Ginting (JISOS: JURNAL ILMU SOSIAL, 2023)
Each region has its own characteristics, which can be in the form of culture, tradition, or culinary. Pematang Siantar, as one of the cities in Indonesia, also has its own unique characteristics. One of the characteristics that continues to grow and survive in this city is the Sarsaparilla Cap Badak drink produced by PT Pabrik Es Siantar. This beverage company has been established since 1916 in Pematang Siantar City, founded by a Swiss chemist named Heinrich Surbeck, who was born in 1876. At the beginning of its establishment, the company was known as NV Ijs Fabriek. In 1971, the Julius Hutabarat family successfully acquired 100% of the shares of PT Pabrik Es Siantar. Under the leadership of the Julius Hutabarat family, PT Pabrik Es Siantar managed to reach its heyday by being able to produce up to 40,000 crates per month. The main markets for Cap Badak drinks are cafes, restaurants, and tourist attractions. This product has become one of the economic supports of the surrounding community, especially in creating quality jobs